Optimalisasi Penggunaan Aplikasi Google Meet dan Zoom Meet Di Masa Pandemi Covid 19 Di Lingkungan Keluarga Besar Group C Paspampres - Sylvia Kartika Dhamayanti (ACADEMICS IN ACTION Journal of Community Empowerment, 2021)
This community service focuses on counselling the extended family of Group C Paspampres Lawang Gintung, Bogor, West Java. It was carried out to optimize the use of Google meet and Zoom cloud meetings in official activities, organizational activities for the wives of Paspampres members, and distance education for the sons and daughters of Paspampres members. This community service is expected to be able to contribute in the form of benefits, namely the opening of an understanding of the use of the Google meet and Zoom cloud meetings applications about how the Zoom cloud meetings and Google meet applications can be optimally used in activities both formally and informally without having to meet face to face during the Covid-19 pandemic. The specific goal of this community is to train the participants so that they can transfer the ability to their children. This community service is aimed at representatives of Paspampres members, civil servants, and wives of Paspampres members in the Paspampres Group C environment to be able to operate the Google meet and Zoom cloud meeting applications optimally so that they can be adapted to their individual needs. To be able to answer the goals of community service, this community service activity was carried out for one face-to-face and demo. The meetings were more focused on limited discussions to gather information about current conditions and expectations in the future, followed by demos using Google meet and Zoom cloud meetings.